The function f(x) = x^3.

To determine f(a+h) substitute x with a+h.

f(a+h) = (a+h)^3

= a^3 +3*a^2*h +3*a*h^2+ h^3

f(a) = a^3

`(f(a+h) - f(a))/h`

= `(a^3+3*a^2*h +3*a*h^2+ h^3 - a^3)/h`

= `(3*a^2*h +3*a*h^2+ h^3)/h`

= `3*a^2 +3*a*h+ h^2`

** The simplified form of `(f(a+h) - f(a))/h` for `f(x) = x^3`...**

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The function f(x) = x^3.

To determine f(a+h) substitute x with a+h.

f(a+h) = (a+h)^3

= a^3 +3*a^2*h +3*a*h^2+ h^3

f(a) = a^3

`(f(a+h) - f(a))/h`

= `(a^3+3*a^2*h +3*a*h^2+ h^3 - a^3)/h`

= `(3*a^2*h +3*a*h^2+ h^3)/h`

= `3*a^2 +3*a*h+ h^2`

**The simplified form of `(f(a+h) - f(a))/h` for `f(x) = x^3` is `3*a^2 +3*a*h+ h^2`**

**Which equals `3a^2` since` ` h = 0.**